Spark plasma sintering of B4C–ZrB2 and B4C–ZrB2–SiC ceramics. (April 2015) - Cheng, Y. H.; Han, W. B.; Liu, D. Z.; An, J. D.; Wang, P.; Zhao, G. D.
<x content-type="archive" xml:space="preserve">Abstract</x> Micrometre-sized B4C powder added with ZrB2 powder or the mixed powders of ZrB2 and SiC were sintered by spark plasma sintering under the load of 30 MPa at 1950°C for 18 minutes. The microstructure and mechanical properties of the composites were investigated. The B4C-20 vol.-% ZrB2 composite showed the highest flexural strength and fracture toughness of 489 MPa and 4·8 MPa·m1/2, were obtained of the B4C-20 vol.-%ZrB2 composite and which were much higher than those of monolithic B4C ceramic. The Vickers hardness of B4C composites ranged from 28·9 to 34·6 GPa. The toughening mechanisms have been analysed because of the deflection of microcrack along with the grains boundary and the mismatch of coefficient of thermal expansion between matrix and additions. Besides, the addition of ZrB2 and SiC was observed to enhance the electrical conductivity and electron discharge machining performance of B4C composites.